Analisis Pembentukan Citra Perusahaan terhadap Community Development (Studi Kasus pada Community Development PT Kimia Farma Tbk) - Peni Anggraelin; Sudharto P Hadi; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2023)
To realize a sustainable business the company prioritizes business ethics. Besides pursuing profit (profit), the company pays attention to the welfare of the wider community (people) and contributes to preserving the environment (planet). These three pillars are embodied in the relationship between business organizations and stakeholders through Corporate Social Responsibility (CSR). The highest level of CSR is community development. The fact is that corporate social responsibility and above is strong enough, what is being questioned is corporate social responsibility to the wider community. PROPER is a government policy to improve environmental management performance in accordance with legislation, in which there is an assessment of community development. In PROPER, obtaining green and gold ratings (beyond compliance) fosters a good image in the eyes of shareholders and stakeholders, blue ratings only achieve the meaning of obedience, red and black ratings indicate disobedience. PT Kimia Farma Tbk, a state-owned pharmaceutical company, received Blue PROPER in 2018 and 2019, indicating that it has complied but has not reached beyond the compliance area. One aspect that needs to be considered is the good or bad community development seen through the corporate image that is formed. The community development of Garbage Bank, Aquaponics and Catfish Livestock in RW 02 Jangli Village is one of PT Kimia Farma Tbk's strategies in fulfilling corporate social responsibility to the wider community. The aim of the research is to know the planning and implementation of community development, to know the impacts that arise and to know the company's PROPER trends in the target group. This type of research is descriptive qualitative with purposive sampling. Data collection by participatory observation, IKM questionnaires and interviews were then analyzed using qualitative analysis. The results showed a positive relationship between SMI ratings, the process of image formation and the image formed. All three showed good results.Untuk mewujudkan bisnis yang berkelanjutan perusahaan mengutamakan etika bisnis. Disamping mengejar keuntugan (profit), perusahaan memperhatiakan kesejahteraan masyarakat luas (people) dan berkontribusi menjaga kelestarian lingkungan (planet). Ketiga pilar tersebut terwujud dalam hubungan organisasi bisnis dengan para stakeholder melalui Corporate Social Responsibility (CSR). Tingkatan CSR tertinggi adalah community development. Faktanya tanggung jawab sosial perusahaan keatas sudah cukup kuat yang dipersoalkan adalah tanggung jawab sosial perusahaan ke masyarakat luas. PROPER merupakan kebijakan pemerintah untuk meningkatkan kinerja pengelolaan lingkungan sesuai perundang-undangan, didalamnya terdapat penilaian community development. Dalam PROPER perolehan peringkat hijau dan emas (beyond compliance) menumbuhkan citra baik dimata shareholder dan stakeholder, peringkat biru hanya mencapai makna taat, peringkat merah dan hitam menunjukkan ketidaktaatan. PT Kimia Farma Tbk, perusahaan farmasi milik negara, mendapatkan PROPER Biru pada 2018 dan 2019, menandakan telah taat namun belum mencapai beyond compliance area. Salah satu aspek yang perlu diperhatikan yaitu community development yang baik buruknya pelaksanaannya dilihat melalui citra perusahaan yang terbentuk. Community development Bank Sampah, Aquaponik dan Ternak Lele di RW 02 Kelurahan Jangli merupakan salah satu strategi PT Kimia Farma Tbk dalam pemenuhan tanggung jawab sosial perusahaan ke masyarakat luas. Penelitian bertujuan mengetahui perencanaan dan implementasi community development, mengetahui dampak yang muncul dan mengetahui tren PROPER perusahaan pada kelompok sasaran. Tipe penelitian yaitu kualitatif deskriptif dengan purposive sampling. Pengumpulan data dengan observasi partisipatif, kuesioner IKM dan wawancara kemudian dianalisis menggunakan analisis kualitiatif. Hasil penelitian menunjukkan hubungan yang positif antar penilaian IKM, proses pembentukan citra dan citra yang terbentuk. Ketiganya menunjukkan hasil yang baik.